Characteristic of Makrozoobenthos and Mangrove Density In the Penebal Village, Bengkalis Sub District, Bengkalis Regency, Riau Province - Eka Dian Fitriani; Nur El Fajri; T. Efrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted in April until Juni 2013 in the Penebal Village. The study aim to understand characteristic of makrozoobenthos (types, abundance, diversity, domination, and equitability) and mangrove density. Method applied was a cases study. Samples of water, sediment fragment, and makrozoobenthos were taken from 3 station, first in the good mangrove forest, second area of mangrove forest wich are already used as shrimp and fish pond , third in the area where most of mangrove has been cut. Parameters measured were abundance, diversity index (H’), dominance index (C), and equitability index (E). Result shown that there were 4 class, consisted of Gastropod (7 species), Bivalve (1 species), Crustacea (1 species), and Polychaeta (2 species). Result shown that makroozoobenthos abundance is strongly related to mangrove density. In the Station 1, the density of mangrove (1.355 trees/ha) as well as that of the makrozoobenthos (146.667 organisms/ha) are the higest. In contrast, in the Stasion 2 the mangrove and the makrozoobenthos abundance are the lowest (322 trees/ha and 50.000 organisms/ha respectively). Water quality parameters in all station slightly different, for station 1 and 2 result of pH is 8 meanwhile for station 3 result of pH is 7. Salinity almost the same is 31 ‰, DO on the range 3,39-4,92. Water temperature, however slightly different, as the stasion 2 (32 °C) is hotter than those of the other station (30 °C in St 1 and 31 °C in St 3).Key words : Makrozoobenthos abundance, Mangrove density, Penebal village